Resolusi Konflik Pilkades Di Madura - Haya Haya (Lembaga Penelitian dan Pengabdian Kepada Masyarakat STI. Blambangan Banyuwangi, 2020)
Abstract This article examines the decisions resulting from the parkades conflict that occurred in Madura. The decision in question is the result of deliberation between the two parties who conflict. Conflicts that occur in a prolonged manner, efforts need to be made to resolve them to find a point of contact, such as bringing together the two parties to express feelings experienced, after which a solution is adopted according to mutual agreement. The research method used is qualitative with a field approach. This study found the following results, to resolve conflicts, conflict needs to be a conflict of interest between two parties or groups that occurred in the Pilkades in Madura. The conflict was triggered by internal and external factors. Conflict is inevitable but managed to become a positive potential. Success in managing conflict makes a developed region. Failure to manage conflict results in prolonged tension. The most important thing in a conflict is the procedure for its resolution. Second, conflict resolution in the Madura Pilkades case is a model for resolution in other regions. The stages of completion include the dialogue and mediation stages. At the dialogue stage, the meeting is conducted by bringing together the interests of the parties to the conflict. Dialogue is held by a third party who can bring these two interests together. Mediation is carried out through guidance and initiatives. Guidance is done formally and informally. Initiative actions are carried out by influential figures by involving the parties concerned.